Kaitan Pemberitaan Yeremia dengan Taurat, Nabi-nabi dan Tulisan-tulisan dalam Perjanjian Lama - Elisamark Sitopu (Jurnal Teologi Cultivation, 2020)
AbstrackThis paper discusses the link between the preaching of the prophet Jeremiah with other parts of the Old Testament, whether it is related to the Torah, the Prophets (Neviim), and the Writings (Khetuvim). The author's assumption is that the preaching of the prophet Jeremiah is inseparable from other parts of the OT. There are passages in Jeremiah that are influenced by the ideas of the earlier OT books, and vice versa Jeremiah also influences the thoughts of the OT books afterwards. In research on this topic, the author uses themethod of library research.Keywords: The message of Jeremiah; Torah; Prophets; Writings.